Language and infant mortality in a large canadian province - Auger, Nathalie; Bilodeau-Bertrand, M.; Costopoulos, A. (Public Health, 2016)
Objectives Infant mortality in minority populations of Canada is poorly understood, despite evidence of ethnic inequality in other countries. We studied infant mortality in different linguistic groups of Quebec, and assessed how language and deprivation impacted rates over time. Study design Population-level study of vital statistics data for 1,985,287 live births and 10,283 infant deaths reported in Quebec from 1989 through 2012. Methods We computed infant mortality rates for French, English, and foreign languages according to level of material deprivation. Using Kitagawa's method, we evaluated the impact of changes in mortality rates, and population distribution of language groups, on infant mortality in the province. Results Infant mortality declined from 6.05 to 4.61 per 1000 between 1989–1994 and 2007–2012. Most of the decline was driven by Francophones who contributed 1.39 fewer deaths per 1000 births over time, and Anglophones of wealthy and middle socio-economic status who contributed 0.13 fewer deaths per 1000 births. The foreign language population and poor Anglophones contributed more births over time, including 0.08 and 0.02 more deaths per 1000 births, respectively. Mortality decreased for Francophones and Anglophones in each level of deprivation. Rates were lower for foreign languages, but increased over time, especially for the poor. Conclusions Infant mortality rates decreased for Francophones and Anglophones in Quebec, but increased for foreign languages. Poor Anglophones and individuals of foreign languages contributed more births over time, and slowed the decrease in infant mortality. Language may be useful for identifying inequality in infant mortality in multicultural nations.

Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

État de la situation et étude de modèles de soins de santé primaires offerts aux francophones vivant en situation minoritaire au Canada - Axion (2016)

Comment améliorer la santé des aînés francophones vieillissant en Ontario ? Entre approche populationnelle et santé communautaire - Bouchard, Louise; van Kemenade, Solange (La santé communautaire en 4 actes : repères, acteurs, démarches et défis, 2016)
fs-ref-orig: Bouchard, L. et van Kemenade, S. (2016). Comment améliorer la santé des aînés francophones vieillissant en Ontario ? Entre approche populationnelle et santé communautaire. Dans V. Desgroseillers, N. Vonarx, A. Guichard et B. Roy (dir.), La santé communautaire en 4 actes : repères, acteurs, démarches et défis (p. 132-137). Presses de l’Université Laval. fs-code-orig: Bouchard-2016

Une réalité qu’on ne peut ignorer : portrait régional des violences faites aux femmes des comtés de Prescott-Russell et les services communautaires disponibles pour les femmes et les familles. Récit d’une recherche-action - Coderre, Cécile (Reflets, 2016)

Health status of minority Francophone seniors in Manitoba and access to services in french: Potential for social isolation - de Moissac, Danielle; Roch-Gagné, Margaux; Ba, Halimatou; Gueye, Ndèye Rokhaya; Ethier, Sophie (Human Development, Disability, and Social Change, 2016)
Francophone seniors in Manitoba represent a growing and vulnerable population, with poorer health outcomes and limited access to health and social services in the official minority language. To avoid isolation, support services are required, as chronic diseases and reduced mobility have a direct impact on both physical and social needs. The purpose of this study is to examine the current health status of seniors in the Francophone minority population of Manitoba and their access to health and social services in French. Demographic, social and health profiles were obtained for Francophone and non-Francophone Home Care clients in Winnipeg. Although diagnosed with similar health conditions as non-Francophones, Francophone seniors are less likely to be assessed with reduced cognitive performance and conditions making mood and behaviour unstable, such as dementia other than Alzheimer’s. Gaps in bilingual health services were identified for pharmacy, audiology and occupational therapy services, meal and transportation systems as well as support services for informal caregivers. Housing options with in-house support services provided in French are available and additionally provide opportunities for seniors to socialize with other Francophones. For the elderly living in singlehome units and their caregivers, support services provided in the official minority language are needed. Keywords: seniors, health, Francophone minority, home care

La précarité des femmes francophones de la région d’Ottawa à travers le prisme de la violence structurelle - Diotte, Sabrina; Flynn, Catherine (Reflets, 2016)
Les inégalités sociales auxquelles font face les populations francophones en Ontario semblent souvent articulées autour de leur condition linguistique minoritaire au sein de la province. Les femmes vivraient de façon plus exacerbée les difficultés liées à cette réalité en raison de la précarité de leurs conditions de vie et de l’accès limité à des services sociaux et de santé dans leur langue (Côté, Lapierre et Levesque, 2015). Cet article propose une analyse intersectionnelle de la précarité des femmes francophones de la région d’Ottawa, à travers le prisme de la violence structurelle. Il montre que leur expérience de la précarité est complexe et est construite autour de plusieurs conditions autres que celle liée à langue. Ces conditions participent également à maintenir ces femmes francophones dans une spirale de précarité. Mots-clés : francophonie, Ontario, femmes, contexte minoritaire, précarité, intersectionnalité, violence structurelle

Comorbidités entre maladies chroniques et problèmes de santé mentale fréquents : différences entre francophones et anglophones - Grenier, Jean; Gosselin, Dominique; Greenman, Paul. Samuel; Chomienne, Marie-Hélène; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Psy-Cause, 2016)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Consommation de drogues, santé mentale et bien-être chez les élèves francophones de l’Ontario selon la SCDSEO de 2015, Études démographiques - Programme de soutien au système provincial (Cyberbulletin, 2016)

Enquête sommaire sur la santé des francophones de Colombie-Britannique - RésoSanté Colombie-Britannique (2016)
fs-ref-orig: RésoSanté Colombie-Britannique. (2016). Enquête sommaire sur la santé des francophones de Colombie-Britannique. fs-code-orig: RésoSanté Colombie-Britannique-2016a

Sortir de la violence conjugale dans l’avancée en âge : les réalités des femmes vivant en milieu rural francophone minoritaire - Savard, Véronique; Marchand, Isabelle (Reflets, 2016)
L’article présente une revue critique de la documentation portant sur les réalités des femmes qui avancent en âge (50 ans et plus), vivent en milieu rural franco-ontarien et sont victimes de violence conjugale, ainsi que sur les enjeux qu’elles rencontrent dans leurs parcours de sortie de violence. Après avoir défini les catégories d’âge retenues, nous montrons notamment que ces femmes sont aux prises avec des contextes sociospatiaux, géographiques et économiques spécifiques, lesquels engendrent des barrières particulières dans la sortie de la violence. De plus, la situation de minorisation vécue sur le plan sociolinguistique accroît certains de ces obstacles, tels que l’accès aux services publics et sociaux. Nous concluons en mettant en relief la dimension critique de la recension effectuée et proposons des pistes de recherche. Mots-clés : violence conjugale, femmes âgées, femmes aînées, femmes qui avancent en âge, baby-boomer, milieu rural, francophone minoritaire

Un filet de sécurité sociale troué : la métaphore de la courtepointe pour raconter des histoires de femmes débrouillardes vivant en situation de pauvreté et qui doivent composer avec une santé fragile - Savoie, Lise; Albert, Hélène; Lanteigne, Isabelle (Reflets, 2016)
Cet article présente des résultats d’une recherche qualitative sur la santé des femmes vivant en situation de pauvreté en régions rurales francophones du Nouveau-Brunswick. C’est à partir de la métaphore de la courtepointe que les auteures ont étudié les contextes dans lesquels les femmes rencontrées développent des stratégies de prise en charge de leur santé. Les résultats soulèvent des enjeux d’ordres collectif et politique, puisque la pauvreté chez les femmes ne constitue pas un problème individuel. Il s’agit d’un phénomène social qui commande des actions structurelles dans un contexte où le filet de sécurité sociale est troué. Mots-clés : femmes, santé, pauvreté, ruralité, débrouillardise sociale, filet de sécurité sociale, métaphore de la courtepointe